Gender Features of Bronchial Asthma in School Age - O.K. Koloskova; T.M. Bilous; H.A. Bilyk (Zaslavsky O.Yu., 2015)
The study of clinical features and determination of markers of inflammation in the bronchi depending on the gender have been carried out in 93 schoolchildren with bronchial asthma. Features of bronchial asthma in school-age boys compared with girls include: three times more frequent onset of the disease in early childhood, eosinophilic phenotype in 66.13 % of cases, the absence of blood eosinophilia (odds ratio (OR) = 3.8) at moderate eosinophilia of sputum (OR = 1.89) with the extracellular accumulation of eosinophilic cationic proteins in sputum that, in general, promotes a better response to administered antiinflammatory therapy. Compared to boys of the same age, in school-age girls the onset of bronchial asthma is more often at the age of 6 years («asthma with late start» - 60.0 %), its atopic form dominated (66.67 %), in peripheral blood of every third patient eosinophilia is determined, girls have tendency to intracellular accumulation of eosinophilic cationic proteins in peripheral blood leukocytes, and the disease is unmanageable, which is determined mainly by the results of self-assessment.